Ethereum Smart Contract Development Build blockchain-based decentralized applications using solidity. - Mukhopadhyay, Mayukh (Packt Publishing, 2018)
Ethereum is a public, blockchain-based distributed computing platform featuring smart contract functionality. In this book, you'll learn about Ethereum and Smart Contracts, and we cover the Ethereum virtual machine (EVM) in detail. Then, you'll get acquainted with DApps and DAOs and they how work. At the end of this book, we discuss ...